A comparison of representations of the imperative of higher education change as transformation"Ÿ versus decolonisation"Ÿ in South African public discourse - Makgakge, Rebecca Dineo (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
The context of higher education in South Africa which has been shaped by the legacies of the old apartheid system is faced with a paramount task of the continuous process of restructuring and change. In shaping the restructuring and change of the higher education system the concept of transformation has been a constant theme for the post-apartheid government policies. However more recently we have seen the heightened prominence of the concept of change understood as decolonisation of South African higher education "“ as opposed to "transformation'. This thesis was concerned with how these concepts of change, "transformation' and "decolonisation' have been used in debates surrounding higher education in South Africa. The thesis compares and contrasts the ways and context in which they are used. This study of 177 South African newspaper articles taken form independent media stables from the time 2008 to the present provides an analysis of representations of higher education change as "transformation' and as "decolonisation' evinced in the corpus. This required using both content and framing analysis as a method to analyse the corpus. Three themes emerged from the analysis that are relevant to the comparison between South African higher education institutional change represented as "transformation' and South African higher education institutional change represented at "decolonisation': the first theme concerns the differences and similarities in how the two terms are defined; the second theme concerns how the two ideas play themselves out when it comes to curriculum change and the final theme concerns the implications of seeing change as "transformation' and seeing change as "decolonisation' for changing institutional cultures.
Keywords: Education in mass media -- South Africa; Higher education and state -- South Africa; Education, Higher -- Curricula -- South Africa; Discrimination in education -- South Africa; South Africa -- Colonial influence; Educational change -- South Africa